Historical Sociology - Mahoney, James (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course provides a broad introduction to the field of historical sociology. The overall objective is to help students understand, appreciate, and critique excellent works of historical sociology. These skills, in turn, should help students, who want to pursue research in this field, to create their own excellent works of historical sociology. This course features weekly assignments, which are included in the materials. The assignments help to focus the discussion, and to ensure that students approach the readings with a least some common issues in mind. In addition, the assignments make certain that all students have a good grasp of essential issues in the field.